2017
DOI: 10.5603/gp.a2017.0018
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal hormone replacement therapy with nanostructured medicines

Abstract: Objectives: Due to hormonal changes during the menopause, women experience a variety of perimenopause and postmenopause symptoms. This review examines the various aspects of nanostructured hormone therapy and its application in the treatments of menopausal symptoms. Material and methods:Excerpta Medica DataBase, Medical Literature Analysis and Retrieval System Online, Web of Science, and Google Scholar were searched basing on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Botelho et.al, 2014 reported that nanostructured formulationof progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause [243]. Abdi et.al, 2017 also concluded that use of transdermal nanoformulations in hormone therapy can relieve climacteric symptoms and prevent other postmenopausal symptoms [245].…”
Section: H Hormone Replacement Therapymentioning
confidence: 99%
“…Botelho et.al, 2014 reported that nanostructured formulationof progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause [243]. Abdi et.al, 2017 also concluded that use of transdermal nanoformulations in hormone therapy can relieve climacteric symptoms and prevent other postmenopausal symptoms [245].…”
Section: H Hormone Replacement Therapymentioning
confidence: 99%
“…Botelho et al, 2014 nanostructured formulation of progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause [223]. Abdi et al, 2017 also concluded that use of transdermal nanoformulations in hormone therapy can relieve climacteric symptoms and prevent other postmenopausal symptoms [226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245].…”
Section: Astaxanthinmentioning
confidence: 99%
“…Also, by increasing skin collagen content, and increasing acid muco polysaccharides and HA, estrogen therapy encourages the growth and development of vaginal epithelial cells which make up the thick layers of the vaginal wall, and condone a moist, supple and elastic environment [242]. Reported that nanostructured formulationof progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause [243], also concluded that use of transdermal nanoformulations in hormone therapy can relieve climacteric symptoms and prevent other postmenopausal symptoms [245].…”
Section: G Poly-l-lactic Acidmentioning
confidence: 99%